Flocking with connectivity preservation of multiple double integrator systems subject to external disturbances by a distributed control law - Dong, Yi; Huang, Jie (Automatica (Oxford), 2015)
This paper studies the flocking with connectivity preservation problem of multiple double integrator systems subject to a class of external disturbances. We solve the problem by a distributed dynamic position feedback control law under the standard assumptions. Our approach is a combination of the potential function technique and observer design. Our result also includes some existing results as special cases.